Prevalence of Salmonella spp. in Vegetables: A Review Paper - Nudar, Mashiyat; Mahboob, Sudipta (Brac University, 2022)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.